How the X-ray spectrum of a narrow-line Seyfert 1 galaxy may be reflection-dominated - Fabian, A. C.; Ballantyne, D. R.; Merloni, A.; Vaughan, S.; Iwasawa, K.; Boller, Th (Monthly notices of the Royal Astronomical Society, 2002)
A model for the inner regions of accretion flows is presented where, owing to disc instabilities, cold and dense material is clumped into deep sheets or rings. Surrounding these density enhancements is hot, tenuous gas where coronal dissipation processes occur. We expect this situation to be most relevant when the accretion rate is close to Eddington and the disc is radiation-pressure-dominated, and so may apply to narrow-line Seyfert 1 (NLS1) galaxies. In this scenario, the hard X-ray source is obscured for most observers, and so the detected X-ray emission would be dominated by reflection off the walls of the sheets. A simple Comptonization calculation shows that the large photon-indices characteristic of NLS1s would be a natural outcome of two reprocessors closely surrounding the hard X-ray source. We test this model by fitting the XMM-Newton spectrum of the NLS1 1H 0707–495 between 0.5 and 11 keV with reflection-dominated ionized disc models. A very good fit is found with three different reflectors each subject to the same Γ=2.35 power law. An iron overabundance is still required to fit the sharp drop in the spectrum at around 7 keV. We note that even a small corrugation of the accretion disc may result in Γ>2 and a strong reflection component in the observed spectrum. Therefore, this model may also explain the strength and the variability characteristics of the MCG–6-30-15 Fe Kα line. The idea needs to be tested with further broad-band XMM-Newton observations of NLS1s.